Pendampingan Pengembangan Usaha Berbasis Teknologi Informasi Untuk Pemberian Pakan Konsentrat - Yaddarabullah Yaddarabullah; Erneza Dewi Krishnasari (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2020)
This activity aims to provide knowledge to Agribusiness department students in developing an information technology-based business aimed at providing concentrate feed. The mentoring provided included how to create an action plan, analyze business models, arrange budget and production needs, build cooperation, and develop Android platform-based applications. This mentoring is given in order to succeed in Agribusiness department students who qualify for a grant from Kemenristekdikti with the Indonesia Student Business Competition (KBMI) scheme in 2019. The result of this mentoring is that students can have sufficient knowledge and resources in running their business.Keywords: Business Development Based on Information Technology, Concentrate Feed